Tattoos, Life Style and the Labor Market - Rik Dillingh; Peter Kooreman; Jan Potters (Institute for the Study of Labor (IZA), 2016)
Placing a tattoo is a choice with potentially significant and long-lasting social and economic consequences. In this study we look at the factors determining the decision to place a tattoo and combine this with several outcomes, such as income and employment status, living together with a partner, (perceived) health and substance use. The analyses are based on unique panel data of a representative sample of Dutch individuals. The tattooed population differs significantly from the non-tattooed population on a wide range of characteristics. The first part of our analysis describes the number, timing, location, size and visibility of tattoos. In the second part we use fixed effects and instrumental variables analysis to explore the effect of tattoos on the above mentioned outcome measures. Our analyses suggest less favorable outcomes for people with (very visible) tattoos, though especially in the case of the labor market, the relationships are relatively weak.
Keywords: J10; J20; 330; tattoos; labor market; health; family; panel data